The Analysis of Doosan S500-LCV Excavator Maintenance Planning to Reduce Downtime Using Reliability Centered Maintenance (RCM) Method - Sidiq Auda; Suparno Suparno (IPTEK Journal of Proceedings Series, 2019)
PT X is a company engaged in construction field and heavy machinery services. PT X uses excavators as a tool to mine rock sand. In 2018, the company has planned to increase production capacity. The increase of production capacity will be directly related to the operational capability of the unit which must always be maintained. The problem in this study is the occurrence of unit downtime that cannot be predicted and occurs in a relatively long time. The components damage of the excavator causes the unit to be unable to operate to increase production. The maintenance of the Doosan S500-LCV excavator at PT X is currently not optimal because the downtime that occurs in the unit is still relatively high. Standard maintenance procedure of excavator units need to be evaluated in order to minimize the occurrence of downtime so that the unit can be used for maximum production. The method used in this analysis is the Reliability Centered Maintenance (RCM) method with evaluating maintenance carried out and giving the right maintenance suggestion. From the results of the analysis and discussion, the critical components of the S500-LCV excavator in PT X are Bucket, Control Valve, Radiator, Alternator and Hydraulic Breaker. Proposed maintenance based on the RCM method and the consideration of S500-LCV maintenance costs at PT X are bucket with preventive maintenance, control valve with a combination of preventive and corrective maintenance, radiator with preventive maintenance, alternator with a combination of preventive and corrective maintenance and hydraulic breakers with preventive maintenance